MODEL PEMBERDAYAAN PETANI MENUJU KETAHANAN PANGAN KELUARGA - Ikeu Tanziha (Food and Nutrition Society of Indonesia, 2011)
The purpose of this study was to analyze the model of farmer empowerment for household food security. Research design was cross sectional, it was conducted in Lebak District on March- November 2010. The data collected was household characteristics, consumption, level of farmer empowerment, and household food security. A systematic stratified random sampling was applied to select 95 farmer households. The path analysis was applied to analyze Model of Farmer Empowerment for Household Food Security. The results showed that 42.1% of farmer household are food insecure, and most of them (52.6%) have low level of empowerment. Model of farmer empowerment for food security can be started with the development and strengthening of megapolitan environment, followed by strengthening the means of production and capital.